Strengthening Confidence, Reducing Deferral: A Relational Model of Self-Regulated Learning, Self-Efficacy, and Academic Procrastination - Kusmawaty Matara; Febriyando Febriyando (Psikostudia : Jurnal Psikologi, 2026)
The phenomenon of academic procrastination among senior undergraduates is a significant issue in the context of higher education because it can hinder the completion of academic assignments and reduce the quality of learning outcomes. This condition is often linked to psychological factors related to self-management skills in learning and individuals’ beliefs regarding their academic abilities. This study aims to test the relational model between self-regulated learning, self-efficacy, and academic procrastination. This study employed a quantitative approach with an explanatory design involving 372 senior undergraduate students in Indonesia selected via purposive sampling. Data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that self-regulated learning has a positive effect on self-efficacy (β = 0.880) and a negative effect on academic procrastination (β = -0.492). Additionally, self-efficacy has a negative effect on academic procrastination (β = -0.440) and was found to partially mediate the relationship between self-regulated learning and academic procrastination (indirect effect = -0.387). Overall, these findings indicate that improving self-regulation skills in learning can strengthen students’ academic confidence, which ultimately contributes to a reduction in procrastination behavior.Fenomena prokrastinasi akademik pada mahasiswa tingkat akhir menjadi isu penting dalam konteks pendidikan tinggi karena dapat menghambat penyelesaian tugas akademik dan menurunkan kualitas pencapaian belajar. Kondisi ini sering dikaitkan dengan faktor psikologis yang berkaitan dengan kemampuan pengelolaan diri dalam belajar serta keyakinan individu terhadap kemampuan akademiknya. Penelitian ini bertujuan untuk menguji model relasional antara self-regulated learning, self-efficacy, dan prokrastinasi akademik.  Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksplanatori terhadap 372 mahasiswa tingkat akhir di Indonesia yang dipilih melalui teknik purposive sampling. Analisis data dilakukan menggunakan Structural Equation Modeling berbasis Partial Least Squares (SEM-PLS). Hasil penelitian menunjukkan bahwa self-regulated learning berpengaruh positif terhadap self-efficacy (β = 0,880), serta berpengaruh negatif terhadap prokrastinasi akademik (β = -0,492). Selain itu, self-efficacy berpengaruh negatif terhadap prokrastinasi akademik (β = -0,440) dan terbukti memediasi secara parsial hubungan antara self-regulated learning dan prokrastinasi akademik (indirect effect = -0,387). Secara keseluruhan, temuan ini menunjukkan bahwa peningkatan kemampuan regulasi diri dalam belajar mampu memperkuat keyakinan akademik mahasiswa, yang pada akhirnya berkontribusi pada penurunan perilaku prokrastinasi.